2004
DOI: 10.1111/j.1471-4159.2004.02789.x
|View full text |Cite
|
Sign up to set email alerts
|

Half‐lives of docosahexaenoic acid in rat brain phospholipids are prolonged by 15 weeks of nutritional deprivation of n‐3 polyunsaturated fatty acids

Abstract: Male rat pups (21 days old) were placed on a diet deficient in n-3 polyunsaturated fatty acids (PUFAs) or on an n-3 PUFA adequate diet containing a-linolenic acid (a-LNA; 18 : 3n-3). After 15 weeks on a diet, [4, H]docosahexaenoic acid (DHA; 22 : 6n-3) was injected into the right lateral cerebral ventricle, and the rats were killed at fixed times over a period of 60 days. Compared with the adequate diet, 15 weeks of n-3 PUFA deprivation reduced plasma DHA by 89% and brain DHA by 37%; these DHA concentrations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
224
4
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(248 citation statements)
references
References 99 publications
(193 reference statements)
19
224
4
1
Order By: Relevance
“…In agreement with this suggestion, one study reported a decrease in brain mRNA expression of DHA-selective iPLA 2 in 24-and 30-month-old rats compared to 4-month-old animals and an increase in pro-inflammatory thromboxane A 2 concentration (Aid and Bosetti 2007), suggesting increased brain DHA half-life due to reduced consumption and upregulated AA metabolism during aging, respectively (DeMar et al 2004). The implication of altered brain AA and DHA metabolism with age on brain PUFA concentrations is controversial since some but not all studies reported age-related changes in PUFA composition in rodents and postmortem human brain (Soderberg et al 1990;Lopez et al 1995;Favrelere et al 2000;Giusto et al 2002).…”
Section: Ementioning
confidence: 64%
See 3 more Smart Citations
“…In agreement with this suggestion, one study reported a decrease in brain mRNA expression of DHA-selective iPLA 2 in 24-and 30-month-old rats compared to 4-month-old animals and an increase in pro-inflammatory thromboxane A 2 concentration (Aid and Bosetti 2007), suggesting increased brain DHA half-life due to reduced consumption and upregulated AA metabolism during aging, respectively (DeMar et al 2004). The implication of altered brain AA and DHA metabolism with age on brain PUFA concentrations is controversial since some but not all studies reported age-related changes in PUFA composition in rodents and postmortem human brain (Soderberg et al 1990;Lopez et al 1995;Favrelere et al 2000;Giusto et al 2002).…”
Section: Ementioning
confidence: 64%
“…A decreased liver synthesis-secretion rate of DHA and the corresponding reduction in plasma unesterified concentration may affect brain PUFA metabolism by decreasing brain DHA consumption and increasing vulnerability to neuroinflammation associated with upregulated AA metabolism, as reported in rats on a low n-3 PUFA diet, which also reduces plasma unesterified DHA concentration (DeMar et al 2004;Rao et al 2007;Kim et al 2011a). In agreement with this suggestion, one study reported a decrease in brain mRNA expression of DHA-selective iPLA 2 in 24-and 30-month-old rats compared to 4-month-old animals and an increase in pro-inflammatory thromboxane A 2 concentration (Aid and Bosetti 2007), suggesting increased brain DHA half-life due to reduced consumption and upregulated AA metabolism during aging, respectively (DeMar et al 2004).…”
Section: Ementioning
confidence: 95%
See 2 more Smart Citations
“…Replacement is proportional to PLA 2 activation and can be imaged by injecting radiolabeled AA intravenously, then measuring regional brain radioactivity by quantitative autoradiography. A regional AA incorporation coefficient k* (regional brain radioactivity/integrated plasma radioactivity), calculated in this way, has been shown to be independent of changes in cerebral blood flow and to represent the plasmaderived AA reincorporated into brain phospholipid (Basselin et al, 2003;Chang et al, 1997;DeGeorge et al, 1991;DeMar et al, 2004a;Rapoport, 2001Rapoport, , 2003Robinson et al, 1992).…”
Section: Introductionmentioning
confidence: 99%